Exploring omissions in nursing care using retrospective chart review: An observational study. (October 2021) - Saar, Lili; Unbeck, Maria; Bachnick, Stefanie; Gehri, Beatrice; Simon, Michael
Abstract: Background: Omissions in nursing care can compromise patient safety. To date, this phenomenon has been investigated almost exclusively via nurse surveys. However, such surveys restrict the range of activities which can be assessed for omissions, and patient level analysis. As an alternative, retrospective chart review methodology has been used successfully in other research fields, but not yet for omitted nursing care. Objectives: To describe characteristics and frequency of omitted nursing care using a retrospective chart review methodology. Design, setting and participants: Observational single center study in two German neurological inpatient units. A random sample of 100 patient admissions was used. Methods: A structured chart review protocol to detect nursing omissions was developed and applied. The full range of expected nursing care activities were assessed regarding the importance of documenting them and whether they had been fully or partially omitted. Vital sign measurements were assessed regarding both the measurement target number and the number of measurements recorded. Results: In total, 1885 activities—a mean of 19 per patient—were identified. Of the reviewed activities, 52% ( n  = 971) were fully or partially omitted. Patients experienced between one and 22 omitted nursing care activities during their hospital stay (8–84% of expected care activities). Ranging from 6% to 100% some activities were more commonly omitted than others during admission. The most frequently omitted nursing activity was giving emotional care (88%, n  = 66); the least frequently omitted was teaching (10%, n  = 29). Vital signs were recorded only 50% ( n  = 141) of the targeted number of times. Conclusions: Using a retrospective chart review protocol to identify omissions in nursing care allows the assessment of a broad range of nursing activities. Additionally, this is the first-time patient-level data on a broad range of activities have been analyzed. The newly developed chart review methodology can complement established survey methods and provide a new perspective on the phenomenon of omitted nursing care.